Vocational Teacher Activities In The Use Of Technology During The Covid 19 Pandemic - Syaiful Haq; Nizwardi Jalinus; Sukardi Sukardi; Syahril Syahril; Rizky Ema Wulansari (International Journal of Educational Dynamics, 2021)
The COVID-19 pandemic presents new challenges to education, especially vocational education. Learning activities could not be done face-to-face, but online learning is an alternative. The regulations governing online learning are of common concern because in vocational education there is not only theoretical learning but also practical learning. This pandemic creates new challenges for the competence of vocational education teachers specifically to be able to use technology to support the implementation of online learning. This research was conducted on vocational education teachers in West Sumatra - Indonesia, examining their competence and use of technology during the pandemic. Samples were taken from six cities; Padang, Bukittinggi, Tanah Datar, Payakumbuh, Agam, and Pariaman. This result shows that teachers always try to improve their competencies during the pandemic by training their self to use information technology in online learning, but it is not easy for them. Teachers still master pedagogical competence, personality competence, professional competence, and social competence. Teachers are more dominant in using computers and smartphones and using WhatsApp and YouTube applications to support the implementation of learning during the pandemic. Teachers must continue to adapt and innovate in online learning using hardware technology as well as the use of offline and online software applications.